"I could not have made it without them": Examining Trainee Cohort Perspectives on MSW Education for Public Child Welfare. Issue 5 (19th October 2016) - Altman, Julie Cooper; Cohen, Carol S.
Abstract : This article reports findings from an evaluation of an MSW child welfare training program focused on increasing retention of knowledgeable, competent and experienced child protective service workers. From qualitative data gathered as part of the process evaluation, we found the cohort effect to be the most salient factor participants experienced as contributing to their successful program completion and their 100% retention rate. Analysis of the cohort effect yielded five themes instrumental in participants' individual and collective success: mutual support, empowerment, belief in self and their finding of a home base which ultimately helped them to launch their professional selves.